کاری توێژەری کۆمەڵایەتی و پەیوەندی بە هاوسەرگیری پێشوەختە توێژینەوەیەکی مەیدانیە لە دادگای سلێمانی - کریم, سازان محمد سعید (Sulaimani Journal for Humanities, 2023)
Premature marriage is a social phenomenon in the history of mankind, and has historical and social evidence that is based on the values of previous nations and until now, but on the contrary, social phenomenon has not been counted and researched The problems that do not cause the disruption of the family balance and dissolved because of these sites that scientific research follows to continue to present the harms of children's lives and the consequences of the family and the consequences in this regard social sciences and social workers. The main purpose of this research is to present the work and duties of social researchers in law and relationship with those who apply for the legalization of early marriage. This research consists of two main gates and several topics related to the research topic Then the second gate, which is about the field aspect of the research, in this research both qualitative and quantitative methods were used (mixed method) and tools (interviews) were used to collect data from all three samples the third sample of the study, then the last section of the field gate is devoted to the results and conclusions.